Effects of aspirin and omega-3 fatty acids on age-related macular degeneration in ASCEND-Eye: a randomised placebo-controlled trial in a population with diabetes - Praveen Patel; Rory Collins; Richard Peto; Mark Davies; Sanjiv Banerjee; David Simpson; John Anderson; Louise Bowman; Peter Scanlon; Amanda Adler; Andrew Farmer; Helen Cook; et al. (BMJ Open)
Purpose Aspirin and omega-3 fatty acids (FAs) are potential disease modifiers of age-related macular degeneration (AMD), but previous studies have produced inconsistent findings. Randomised evidence for the efficacy and safety of aspirin and omega-3 FAs on AMD is presented in this study.Design ASCEND-Eye is a substudy of eye effects in the 2×2 factorial design ASCEND (A Study of Cardiovascular Events iN Diabetes) double-blind, randomised, placebo-controlled trial for the primary prevention of cardiovascular events. Reports of AMD diagnoses were sourced from 6 monthly ASCEND follow-up questionnaires and a Visual Function Questionnaire.Participants 15 480 UK adults at least 40 years of age with diabetes but no evident cardiovascular disease.Interventions 100 mg aspirin daily versus placebo and, separately, 1 g omega-3 FAs daily versus placebo.Main outcome measure The first post-randomisation reports of AMD.Results During 7.4 years of follow-up, 122 (1.6%) participants randomised to aspirin were reported as having AMD, compared with 138 (1.8%) randomised to placebo (rate ratio 0.88; 95% CI 0.69 to 1.12; p=0.31). AMD occurred in 130 (1.7%) participants randomised to omega-3 FAs, compared with 130 (1.7%) randomised to placebo (rate ratio 0.99; 95% CI 0.78 to 1.27; p=0.99).Conclusion No clinically-meaningful effects of aspirin or omega-3 FAs on AMD were found. Although the study had very limited statistical power to detect clinically relevant effects, these data overcome some methodological limitations of previous observational studies, providing randomised evidence of both treatments on AMD, which could contribute to future meta-analyses.Trial registration number ISRCTN60635500 and NCT00135226.